Assessment of the bidirectional causal association between Helicobacter pylori infection and allergic diseases by mendelian randomization analysis - Guo Zhen Fan; Bo Yang Duan; Fang jie Xin; Zheng Hai Qu (Scientific Reports)
Abstract This article employed a bidirectional Mendelian randomization (MR) analysis to deduce the causal relationship between H. pylori infection (Seven H. pylori antibodies: CagA, Catalase, GroEL, IgG, OMP, UREA, and VacA) and allergic diseases. This study primarily employed the Inverse-Variance Weighted (IVW)method, supplemented by MR-Egger regression and the Weighted median (WM) method approach, to comprehensively assess the causal relationship between exposure and outcome. Sensitivity analysis, including Cochran’s Q test, MR-Egger regression intercept, MR-PRESSO test, and leave-one-out analysis, verified the reliability of the results. In the forward MR analysis, the IVW analysis outcomes showed the causal relationship existed between the allergic urticaria (AU) and Catalase antibody, allergic asthma (AA) and allergic rhinitis (AR) with OMP antibody, and allergic conjunctivitis (AC) and VacA antibody; in the reverse MR analysis, the results of the IVW analysis revealed that CagA antibody was positively associated with AU. Sensitivity analysis indicated that the causal relationship was robust. Higher levels of Catalase antibody may potentially increase the risk of AU development; increased OMP antibody levels might be associated with a higher risk for AA, yet could potentially be a protective factor against AR; greater VacA antibody levels might possibly decrease the incidence of AC; individuals with AU might have a higher likelihood of exhibiting elevated CagA antibody levels. It is suggested that H. pylori infection could potentially influence the onset and progression of allergic diseases via the “gut-skin”, “gut-lung”, “gut-nose”, and “gut-eye” axis; moreover, skin diseases may potentially impact the gut microbiota imbalance through the “skin-gut” axis.